The evaluation of the use of jack bean (Canavalia ensiformis) and protease enzyme on the broiler diet with the different level of protein - Mahardhika, Brahmadhita Pratama; Ridla, Muhammad; Mutia, Rita; Febriani, Sisca; Purbaya, Agung Mayandika (Livestock and Animal Research, 2023)
Objective: This study evaluated the use of jack beans (Canavalia ensiformis) and protease enzymes in broiler chicken feed. The protein levels on carcasses and the efficiency of the diet were assessed based on protein efficiency ratio, nitrogen retention, percentage of immunity organs, and feed economic analysis based on Income Overfeed Conversion.Methods: The factorial complete randomized design (CRD) was employed in this study, piloting three treatment factors: protein level (22% and 19.5%), protein source material (basal diet and jack bean), and the use of enzymes (without enzymes and protease supplementation). Moreover, three replications were conducted, consisting of two samples of broiler chickens per replication. Forty-eight male broiler chickens from 240 populations that had previously been reared for 28 days were taken as the sample of the study.Result: The results showed that the use of jack beans significantly decreased the dress body weight (P<0.05), undress body weight, and carcass weight of broiler chickens. In addition, the weight significantly increased IOFC by (P<0.01). The use of protease enzymes significantly (P<0.05) increased Retention Nitrogen, Protein Eficiency Ratio, and carcass. The feed protein level decreased substantially by (P<0.01). It reduced protein consumption, RN, PER, dress, undress, and carcass body weight. The use of jack bean did not affect the broiler's immune organ size.Conclusion: The use of protease enzymes in diets with low protein levels can produce dress body weight, carcass body weight, RN, and PER, similar to basal diets, without affecting the size of the immune organs of broiler chickens.